The Effect of Ginger Compress On Reducing The Pain Scale of Gout Sufferers (Literatur Review): The Effect of Ginger Compresses On Reducing The Pain Scale of Gout Sufferers (Literatur Review) - Yani Trihandayani (Journal of Vocational Health Science, 2024)
Background: The incidence of gout in the world has reached 335 million people. Uric acid is the result of purine metabolism in the body whose levels should not be excessive. The pain that arises in gout is part of the joints. One of the treatments of pain due to nonpharmacological uric acid is to use traditional remedies such as ginger. Purpose: The purpose of this literature is to analyze the effect of ginger compresses on reducing the pain scale in gout sufferers. Methods: This research method is literature review through the google scholar database (2015-2021), using the keywords:"ginger compress AND Pain AND Gout". 9 journals were obtained according to the established inclusion criteria. Results: Results from 9 journals to be reviewed on average published in 2017/2018, the research design mostly uses experimental Quasy. The sampling technique uses total sampling, with questionnaire instruments. Data analysis using paired t-test. Of the 9 journals reviewed, it was stated that there was an effect of ginger compresses on reducing the pain scale. Conclusion: From the 9 journals reviewed, there was a significant influence between ginger compresses and pain reduction. The same results stated that there was a significant comparison before and after ginger compresses to the reduction of pain in gout sufferers. Keywords: ginger compress, Pain, Gout.